How to price effectively : a guide for managers and entrepreneurs - Dholakia, Utpal (Ascent Audio, 2021)
Pricing decisions are among the most important and impactful business decisions that a manager can make. How to Price Effectively: A Guide for Managers and Entrepreneurs introduces the value pricing framework, a structured, versatile, and comprehensive method for making good pricing decisions and executing them. The framework weaves together the latest thinking from academic research journals, proven best practices from the leading pricing experts, and ideas from other fields such as medical decision making, consumer behavior, and organizational psychology. The book discusses what a good pricing decision is, which factors you should consider when making one, the role played by each factor-costs, customer value, reference prices, and the value proposition- and how they work together, the importance of price execution, and how to evaluate the success of pricing decisions. You will also be introduced to a set of useful and straightforward tools to implement the value pricing framework, and study many examples and company case studies that illustrate its nuances. The purpose of How to Price Effectively: A Guide for Managers and Entrepreneurs is to provide you with a comprehensive, practical guide to making, executing, and evaluating pricing decisions.